Associação entre autorreferência a distúrbio de voz, desvantagem vocal e Síndrome de Burnout em líderes e obreiros religiosos - Lima, Aleandra Cardoso (2015)
to analyze the association between self-reported voice disorder (VD), voice handicap and Burnout Syndrome in religious leaders and workers of a Pentecostal Christian church. Method: this is a cross-sectional, descriptive study that has been approved by the Research Ethics Committee at PUCSP and had the participation of 197 subjects of both genders, above 18 years of age. Data collection was conducted at the Assembleia de Deus Pentecostal Christian Church of the city of Sorocaba/SP, between the months of April and May, 2014. The following instruments were used: a questionnaire in order to survey socio-demographic data and the religious leaders work situation; the Screening Index for Voice Disorder (SIVD); Voice Handicap Index (VHI 10) and the Malasch Burnout Inventory (MBI).The latter is divided into the three following dimensions: Emotional Exhaustion (EE), Depersonalization (DP) and Personal Accomplishment (PA). The data were typed and analyzed (SPSS version 17.0 for Windows), according to their absolute and relative frequencies, central tendency and dispersion measurements. The chi-square test, as well as binary univariate and multivariate logistic models were used in order to verify the association between the independent variables (socio-demographic and work situation data, VHI and MBI) with the VD outcome (stratified into without VD < 4 and with VD ≥5 ). Results: of the 197 subjects, most are male (77.2%), with mean age of 43.4 years (sd=11.1), married (88.4%), with High School education (56.6%), with another professional activity besides ministry (73,1%), with a mean time in the job of 7.5 years (sd=7.6). Concerning the SIVD, 40.1% had a chance of developing VD (SIVD). The VHI 10 was divided into four quartiles, and the results were: 1st quartile (values 0) = 50 (25.4%); 2nd quartile (1 to 3) = 53 (26.9%); 3rd quartile (4 to 6) =46 (23.3%); and 4th quartile (≥ 7) = 48 (24.4%). Religious workers and leaders in the 3rd and 4th quartiles had chance of possibly having a VD when compared to the subjects in the 1st quartile of, respectively, OR=2.59 (p=0.041) and OR=5.82 (p<0.001). Regarding the MBI, for EE and DP dimensions, most religious subjects had low levels, respectively 69.5% and 54.3%, and 44.7% high degree for PA, although none was associated to the variable VD. Concerning age, the religious subjects who were 44 or older had a chance (OR = 1.99; p=0.041) of having VD when compared to younger religious subjects. Being single has also proved an independent factor for VD (OR=4.08; p=0.014), adjusted by the Burnout exhaustion variable. Conclusion: In this study conducted with 197 Christian religious individuals who work in different areas in the church, there was association between the presence of a possible voice disorder and self-reported voice handicap, where the increase in handicap was proportional to the chance of having a disorder. There was no association between the presence of a possible voice disorder and Burnout syndrome. In the logistic regression analysis the possible presence of voice disorder was more likely present among the eldest and single individuals